2015
DOI: 10.1080/00223891.2015.1029072
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Anhedonia in Adolescents: A Psychometric Analysis

Abstract: Anhedonia—the reduced capacity to experience pleasure—is a trait implicated in mental and physical health. Yet, psychometric data on anhedonia measures in adolescents are absent. We conducted an in-depth psychometric analysis of the Snaith-Hamilton Pleasure Scale (SHAPS; Snaith et al., 1995)—a self-report measure of anticipated pleasure response to 14 pleasant experiences—in adolescents. Adolescents (N=585; M age=14.5) completed the SHAPS and other paper-and-pencil surveys. Item response theory models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 56 publications
3
52
0
1
Order By: Relevance
“…Each study measure described below has shown good psychometric properties in previous adolescent samples (Audrain-McGovern et al, 2004; Bastiani et al, 2013; Eaton et al, 2010; Johnston et al, 2015; Leventhal et al, 2015 in press; Martino, Grilo, & Fehon, 2000; Muris & Meesters, 2008; Pang, Farrahi, Glazier, Sussman, & Leventhal, 2015 in press; Wagner et al, 2006; White & Labouvie, 1989). Unless otherwise specified, a mean score per item composite was calculated and composites were scored such that higher scores reflect higher psychopathology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each study measure described below has shown good psychometric properties in previous adolescent samples (Audrain-McGovern et al, 2004; Bastiani et al, 2013; Eaton et al, 2010; Johnston et al, 2015; Leventhal et al, 2015 in press; Martino, Grilo, & Fehon, 2000; Muris & Meesters, 2008; Pang, Farrahi, Glazier, Sussman, & Leventhal, 2015 in press; Wagner et al, 2006; White & Labouvie, 1989). Unless otherwise specified, a mean score per item composite was calculated and composites were scored such that higher scores reflect higher psychopathology.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the transdiagnostic phenotype measures described below has been consistently associated with multiple psychopathologies (Audrain-McGovern et al, 2009; Audrain-McGovern et al, 2004; Cyders et al, 2007; Ellis & Rothbart, 2001; Isolan, Salum, Menezes Flores, de Carvalho, & Gus Manfro, 2012; Leventhal et al, 2015 in press; Leyro, Zvolensky, & Bernstein, 2010; Muris et al, 2008; Muris, Schmidt, Merckelbach, & Schouten, 2001; Pang et al, 2015 in press; Smith et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Average of scores from 3 items indicating the “reduced ability to experience pleasure in response to rewarding stimuli” (Leventhal et al, 2015, p. 1). Participants responded to “Indicate how much pleasure/enjoyment you would feel right now in response to…” spending time with people close to you”, “personal hobbies”, and “socializing” were used (α=.81).…”
Section: Methodsmentioning
confidence: 99%
“…This 3-item self-report scale (Leventhal et al, 2015), adapted from the Snaith-Hamilton Pleasure Scale (Snaith et al, 1995), included items that inquired about experiencing pleasure or enjoyment from small things (“a bright sunny day or a telephone call from a friend”), nature (“a beautiful landscape or view”), and receiving praise from others. Items were answered with a Likert format (1 = Strongly Agree to 4 = Strongly Disagree ), with higher sum scores indicating greater levels of trait anhedonia.…”
Section: Methodsmentioning
confidence: 99%